Piecemeal Deglutition and the Implications for Pressure Impedance Dysphagia Assessment in Pediatrics. Issue 6 (December 2018) - Ferris, Lara; King, Sebastian; McCall, Lisa; Rommel, Nathalie; Scholten, Ingrid; Teague, Warwick; Doeltgen, Sebastian; Omari, Taher
ABSTRACT: Objectives: High-resolution impedance manometry (HRIM) enables biomechanical swallow assessment. Piecemeal deglutition (PD) defines swallowing of a single bolus in 2 or more portions. We investigated PD sequences on HRIM recordings to ascertain appropriate swallow selection for analysis and to determine the impact of PD on swallow function measures. Methods: Pharyngo-esophageal motility and bolus flow were assessed in 27 children (19 M, mean age 15 months) with repaired esophageal atresia and trachea-esophageal fistula, but who were asymptomatic of oropharyngeal dysphagia. A consistent volume of between 2 and 5 mL saline boluses was given to each patient. Retrospectively, PD sequences were defined based on the number of swallows required to clear the bolus from the oral cavity: pattern A = 1–2 swallows; pattern B = 3 swallows; and pattern C = 4+ swallows. The largest bolus volume swallowed was noted as the dominant swallow in each pattern. Pressure Flow Analysis defined contractility, distension and flow timing metrics. Data were averaged for each PD pattern, and compared with dominant swallows from each pattern. Results: PD pattern B (43.7%) was the most prevalent across the cohort. PD patterns were similarly distributed across age groups (G1: <1 years, G2: 1–4 years). Differences in upper esophageal sphincter distension and pharyngeal flow timing measures were, however, seen in relation to both age and PD pattern, whereby a larger pharynx in older children elicited greater distension for a longer latency, and for larger volumes. Conclusions: PD reduces bolus volume, and biomechanical swallow measures are impacted. PD is a necessary consideration for accurate HRIM analysis of swallow function. Selection of dominant swallows from a PD sequence provides a swallow profile which best represents a child's swallow function, and should always be reported and interpreted in context of the PD sequence observed. Abstract : Supplemental Digital Content is available in the text